Disease of the island of Meleda or keratoderma of Meleda - Indira N. Abduvaxitova; G'ayratillo Sh. Toxtayev; Kholikjon Kh. Safarov (State Scientific Center of Dermatovenereology and Cosmetology, 2020)
Keratoderma is a group of dermatoses characterized by a violation of keratinization processes, excessive horn formation mainly in the area of the palms and soles. Under our supervision in the Tashkent regional skin and venereal clinic in the Department of dermatology was a patient Z. born in 2007, who was undergoing inpatient treatment for Meleda island disease. The rash is localized in the area of the palm and soles, changes and dystrophy of the nails. As a result of inpatient treatment (12 days), the Horny layers on the palms and soles decreased, especially in the Central part. All the cracks have fused, no new ones have been found. The severity of inflammatory phenomena, hyperkeratotic layers decreased, the area of the lesion and the intensity of itching decreased. The patient was discharged from the hospital with clinical improvement. This case is of particular interest to practical dermatovenerologists as a rare dermatosis